2020
DOI: 10.1186/s12966-020-00936-5
|View full text |Cite
|
Sign up to set email alerts
|

Compositional analysis of the associations between 24-h movement behaviours and cardio-metabolic risk factors in overweight and obese adults with pre-diabetes from the PREVIEW study: cross-sectional baseline analysis

Abstract: Background: Physical activity, sedentary time and sleep have been shown to be associated with cardio-metabolic health. However, these associations are typically studied in isolation or without accounting for the effect of all movement behaviours and the constrained nature of data that comprise a finite whole such as a 24 h day. The aim of this study was to examine the associations between the composition of daily movement behaviours (including sleep, sedentary time (ST), light intensity physical activity (LIPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 36 publications
3
25
1
Order By: Relevance
“…Limited research using the ISM in older adults is available and only, isolated reports in general adult populations with chronic conditions, such as the MetS [44,45], or using data from DXA scans are available [32]. However, no research using the same methods as this study in older adults has been found, limiting the opportunities for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research using the ISM in older adults is available and only, isolated reports in general adult populations with chronic conditions, such as the MetS [44,45], or using data from DXA scans are available [32]. However, no research using the same methods as this study in older adults has been found, limiting the opportunities for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research using the ISM in older adults is available, and only isolated reports in general adult populations with chronic conditions, such as the MetS [ 44 , 45 ], or using data from DXA scans are available [ 32 ]. However, no research using the same methods as this study in older adults has been found, limiting the opportunities for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it remains an unanswered question if there are longterm effects of different exercise intensities on subjective appetite sensations. Further analyses on associations between PA and appetite irrespective of allocation are needed (62). Furthermore, as standard meals were not provided, all our results were based on memory recall of overall appetite sensations in the fasting and postprandial state during the previous week.…”
Section: Discussionmentioning
confidence: 99%